STUDY REGARDING TOOTH SHADE MATCHING USING DIGITAL DENTAL PHOTOGRAPHY - Kinga Mária Jánosi; Diana Cerghizan; Laura Valentina Budușan; Adriana Elena Crăciun; Monica Dora Baloș; Liana Georgiana Hănțoiu; Izabella Mureșan; Aurița Ioana Albu (Romanian Journal of Oral Rehabilitation, 2022)
Choosing the right color is crucial in oral rehabilitation. Shade matching has often been a dilemma in the past but remained a crucial procedure even in our daily practice, especially in the case of frontal restorations. Digital photography is a common way of communication between medical team members and could be used in dental practice with a high success rate for accurate shade selection. The study aims to qualitatively compare the L*, a*, and b* values of shade matching obtained by digital photographs with two different devices: a smartphone (with flash and without flash) and a digital camera using the Vita Classical shade guide. The results showed that a correctly set DSLR camera could be used successfully to perform shade matching; older smartphones with automatic settings are not suitable for shade matching.